Cashew Yogurt sebagai Bahan Pangan Fungsional yang Menunjang Good Life Style pada Anak - Seventina Nurul Hidayah; Adevia Maulidya Chikmah; Umriaty Umriaty (Prodi D III Kebidanan Fakultas Ilmu Kesehatan Universitas Ibrahimy, 2022)
Adequate toddler nutritional intake is a major contribution to nutritional status and health status. Yogurt is a nutrient-rich intake with more nutritional quality than milk because it is easily digested and has therapeutic. Cashews contain chemical compounds that are useful as antibacterial and antiseptic. From several research results there is a gradual increase in calcium, magnesium, sodium and manganese in cashew milk yogurt which can support Life Style. Descriptive research with a population of 25 children in Karanganyar village who are willing to eat samples of cashew yogurt given to them. The sampling technique was Total Sampling, Research Instruments and the instrument used in this study was a questionnaire to obtain organoleptics from cashew yogurt (taste, color, aroma, appearance, consistency), development and good life style. The Good Life Style studied in this study are Body Mass Index, children's sleep patterns, sports activities, consumption patterns of food/drinks containing 5P, use of gadgets,and health or growth checks of children. The results showed that respondents tended to have a normal body index,because during the pandemic, respondents were only at home.This research has several stages, namely making yogurt work starters, making cashew yogurt, ph test, and organoleptic test. In making yogurt stsrter we use purple cabbage for making cashew yogurt. The cashew yogurt application is used as a salad dressing (thick yogurt).The taste of cashew yogurt is delicious as much as 48%,while the taste of ordinary cow yogurt is 36% which can be used as functional food that supports a child's good life style.